Clostridium autoethanogenum protein inclusion in the diet for broiler: Enhancement of growth performance, lipid metabolism, and gut microbiota - Wu, Yushan; Wang, Jing; Jia, Ming; Huang, Shixin; Cao, Ying; Yao, Ting; Li, Junguo; Yang, Yuxin; Gu, Xu (Frontiers in Veterinary Science, 2022)
This study aimed to investigate the effects of dietary supplementation of new single-cell protein Clostridium autoethanogenum Protein (CAP) on growth performance, plasma biochemical indexes, liver histology, lipid metabolism and gut microbiota in Cobb broilers. According to the randomized block experimental design, 960 Cobb broilers (1d old) were divided into 6 different treatments with 8 replicates of 20 birds each. Six isonigrogenous and isoenergetic diets were formulated with different contents of CAP (0, 1, 2, 3, 4 and 5%) to replace soybean meal (SBM). The results showed the addition of CAP didn’t influence liver health when exceeded 2%, and the protein metabolism markers and feed conversion rate increased (P < 0.05), which significantly improved the growth performance. When the content of CAP were greater than 4%, it could promoted lipolysis without affecting lipogenesis, resulting in the decrease of abdominal fat rate. There was no significant difference in MDA between these groups (P = 0.948). The increase of SOD and GSH-Px indicated the enhancement of antioxidant response. Alpha diversity did not show a significant difference between groups (P > 0.05). Inclusion 4% or less CAP led to the increase in beneficial microbiota, the concentration of short-chain fatty acids (SCFAs) such as acetic acid, propionic acid and butyric acid (P < 0.05) and the concentration of primary bile acids such as cholic acid and goose deoxycholic acid (P < 0.05). While the concentration of secondary bile acids such as taurocholic acid and taurine goose deoxycholic acid were decreased (P < 0.05). These results illustrated that the CAP had high potential for application in poultry nutrition. In terms of improving growth performance and antioxidant capacity and reducing fat deposition rate, 4% CAP content is recommended.